Muscat-Omani relations - Wingate, Ronald Evelyn; Alban, Reginald George; Bremner, Claude Edward U; Āl Bū Sa‘īd, Sa‘īd bin Taymūr (British Library, 1932)
Correspondence discusses relations between Muscat state and the interior of Oman. Since 1920 the Treaty of Sib had regulated the interactions between Muscat on the coast and the interior of Oman under the Imam. The treaty was mediated by Ronald Evelyn Wingate, Political Agent, Muscat. Correspondence in 1945 and 1946 discusses Sultan Sa'id bin Taimur's desire to obtain a guarantee of RAF support for any incursion into the interior when the ailing Imam died. Letters from British officials discuss what additional leverage they could gain as a condition of provision of arms and officers. Correspondents include Shaikh Isa bin Saleh (of Sur); Reginald George Alban, Political Agent Muscat; Major Claude Edward U Bremner, Political Agent Muscat.
Keywords: Traité de Sib

La Tunisie d'il y a cinquante ans d'après les notes et souvenirs du commandant Varloud du 4e régiment de zouaves - Varloud, Jacques (Berger-Levrault, 1932)
Keywords: Récits de voyage -- Djerba

La France en Tunisie au XVIIe siècle : Correspondance de Nicolas Béranger de Marseille, marchand à Tunis (1692-1700) - Grandchamp, Pierre (Inventaire des Archives du Consulat de France à Tunis, 1932)